Synthesis, morphology, structure, and magnetic characterization of layered cobalt hydroxyisocyanates. - Du, Y; O'Hare, D (2008)
New layered pink cobalt hydroxyisocyanates have been prepared by controlled hydrolysis of aqueous solutions of CoCl2.6H2O. Co(OH)(1.4)(NCO) 0.6.0.6H 2O ( 1) is formed when urea is used as the hydrolysis agent and mannitol as the stabilizer, while Co(OH)(1.25)(NCO)(0.75).0.2H2O ( 2) is formed when the hydrolysis agent is changed to hexamethylenetetramine and NaOCN is added to the solution. IR spectroscopy of 1 and 2 indicates that the OCN (-) is N-bonded to Co (2+). The X-ray powder data for 1 could be indexed using an intergrowth model consisting of both rhombohedral ( R3 m (166); a = 3.2031(1) A, c = 23.6876(11) A, hydrotalcite-like, 3 R 1) and hexagonal ( P 63/ mmc (194); a = 3.2005(2) A, c = 15.8303(5) A, Manasseite-like, 2H1) polytypes. Rietveld refinement of the X-ray powder data was performed using a two polytype model and 30% random substitution of the OH (-) ions by OCN (-). Although it is less crystalline, the XRD data for 2 can be indexed using a rhombohedral-symmetry cell with unit cell parameters, a = 3.158 A and c = 21.57 A. Both 1 and 2 exhibit magnetically ordered ground states with a saturation magnetization of ca. 2.0 mu B. The magnetization data is consistent with 3D ferromagnetic ordering of edge-share octahedral-Co (2+) layers with effective spin S' = 1/2.